Dietary molasses enhances ruminal biohydrogenation and partially alleviates diet- induced milk fat depression - Bradford, Barry J.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Milk fat depression remains a problem on dairy farms, and in recent years, incorporation of distillers grains (typically with solubles added and often dried) has contributed to this problem on some farms. In this study, we evaluated whether molasses could prevent milk fat depression in cows fed a high-risk diet. Replacing up to 5% of dietary corn with cane molasses linearly increased the yield of short- and medium-chain fatty acids in milk, indicating a positive effect on de novo fatty acid synthesis in a milk fat depression environment. Molasses, however, tended to linearly decrease milk yield and linearly decreased milk protein yield, resulting in no net effect on energy- or solids-corrected milk yield. These results indicate that the potential exists for sources of dietary sugar to prevent milk fat depression, but further research is needed to determine when sugar sources might be most effective.
Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy; Dietary molasses; Ruminal biohhydrogenation; Milk; Depression